THE PHENOMENON OF POST-FOLKLORE IN THE FOLKLORE OF THE UZBEK WEDDING CEREMONY (American Journal of Interdisciplinary Research and Development, 2023)
In the article, socio-political changes in the society, acceleration of development and processes of globalization are analyzed as factors that caused the observation of the post-folkloric phenomenon in the folklore of the Uzbek wedding ceremony.